PSV-5 Effect of oxygen administration to piglets at birth on post-natal body temperatures. (30th November 2020) - Cooper, Naomi; Vande Pol, Katherine; Ellis, Michael; Xiong, Yijie; Gates, Richard
Abstract: Newborn piglets are susceptible to hypothermia, and associated mortality. Previous research suggested exposing neo-natal piglets to elevated oxygen concentrations reduced post-natal body temperature decline. This study evaluated the effects of oxygen administration at birth on piglet temperatures over 24 h after birth. This study used 296 piglets (24 litters) and was carried out in a standard farrowing facility consisting of crates within pens with a heat lamp. A GRBD was used; sow was the blocking factor; piglet the experimental unit. A replicate was 3 littermates of similar BW; piglets were randomly allotted at birth within replicate to treatment: 1) Control [dried at birth (with a desiccant); returned to farrowing pen]; 2) Ambient Oxygen (dried; placed in a chamber at ambient temperature and oxygen concentration for 20 min); 3) 40% Oxygen (dried; placed in a chamber at ambient temperature and 40% oxygen concentration for 20 min). Piglets were weighed at birth. Rectal temperature was measured at 0, 20, 30, 45, 60, 90, 120, 180, 240 and 1440 min after birth. Data were analyzed using PROC MIXED of SAS. The model included fixed effects of treatment, time of measurement (repeated measure), and the interaction and random effects of block and replicate. There was no treatment effect (P > 0.05) on temperatures at birth and between 120 and 1440 min. Compared to the Control, temperatures were lower (P < 0.05) for the 40% Oxygen treatment between 20 and 90 min and for the Ambient Oxygen treatment between 20 and 45 min. Temperatures at 60 and 90 min for the Ambient Oxygen treatment were intermediate to and not different (P > 0.05) from the other treatments. Results suggest that exposing neo-natal piglets to an oxygen-rich environment in a chamber does not reduce post-natal temperature decline. This research was funded by the National Pork Board.